2012
DOI: 10.1039/c2cc17909a
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent sensor for selective detection of cyanide using mesoporous graphitic carbon(iv) nitride

Abstract: A turn-on fluorescence sensor, Cu(2+)-c-mpg-C(3)N(4), was developed for detection of CN(-) in aqueous solution by simply mixing cubic mesoporous graphitic carbon nitride (c-mpg-C(3)N(4)) and aqueous solution of Cu(NO(3))(2). The highly sensitive detection of CN(-) with a detection limit of 80 nM is not only possible in aqueous solution but also in human blood serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 26 publications
2
64
0
Order By: Relevance
“…Unlike the traditional carbon materials, g-C 3 N 4 possesses a stacked two-dimensional structure and can be regarded as a promising source for the mass-production of free-standing nitrogen-rich carbon materials, which is propitious to disperse and stabilize the Pd nanoparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the traditional carbon materials, g-C 3 N 4 possesses a stacked two-dimensional structure and can be regarded as a promising source for the mass-production of free-standing nitrogen-rich carbon materials, which is propitious to disperse and stabilize the Pd nanoparticles [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The modification of -NH-, =N-,-NH 2 groups existing on the surface of g-C 3 N 4 is highly responsible for its enhanced optical properties [33][34][35] Gillian et al 36 reported that g-C 3 N 4 is stable in water, THF, ethanol, diethyl ether, toluene etc. Among different forms of g-C 3 N 4 , mesoporous carbon nitride has large surface area and suitable semiconductor towards the application of heterojunction construction 32 .…”
Section: Graphitic Carbon Nitride (G-c 3 N 4 )mentioning
confidence: 99%
“…Cubic mesoporous ordered g-C 3 N 4 as an all-in-one chemosensor was used for the detection of trace amounts metal ions [23]. Semiconductor properties of g-C 3 N 4 nanosheets were explored to design fluorescence sensors for sensitive and selective detection of Cu 2+ [24,25]. Recently, the g-C 3 N 4 has been used as a highly sensitive electrochemical sensor for simultaneous electrochemical detection of Pb 2+ , Cu 2+ and Hg 2+ by modifying glassy carbon electrode [26].…”
Section: Introductionmentioning
confidence: 99%